The Integration of AI Technology in Implementation Inde-pendent Curriculum - Nuorma Wahyuni; Erlin Setyaningsih; Dila Seltika Canta; Adi Hermawansyah; Sudarman Sudarman (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Artificial Intelligence (AI) or commonly known as intelligence artificial is something that allows the machine to can do working that can done by humans . In the development of digital technology, AI brings major influence on the sector education . Where AI makes the learning process take place more adaptively , individually, and efficiently so that support transformation education in the digital era. This research aims For study AI concepts in context education , analyzing its suitability with the characteristics of the Independent Curriculum, as well as identify various Benefits and challenges in applying AI to the learning process . The method used was library research , which examined several scientific articles relevant to the research topic . The data was analyzed . For get description about AI integration in the implementation of the Independent Curriculum. Study results shows that AI has important role in supporting personal learning , technology-based assessment , development of teaching materials, and improvement effectiveness of the teaching and learning process. In addition, AI contributes to improving competence teacher pedagogy , digital literacy , creativity , and critical thinking skills student. However , the implementation of AI is still face various challenges , including limited technological infrastructure, digital access gap, low educator technology literacy , as well as issue ethics and data privacy . Therefore , it is necessary improvement digital competency , infra-structure support, and clear regulations so that the integration of AI in the Independent Curriculum can run optimally and sustainably in improving quality education in Indonesia.